MRI topography of lesions related to internuclear ophthalmoplegia in patients with multiple sclerosis or ischemic stroke - Kleinsorge, Marie Therese; Ebert, Anne; Förster, Alex; Weber, Claudia Ellen; Roßmanith, Christina; Platten, Michael; Gass, Achim; Eisele, Philipp (Journal of neuroimaging, 2021)
Background and Purpose Internuclear ophthalmoplegia is a dysfunction of conjugate eye movements, caused by lesions affecting the medial longitudinal fasciculus (MLF). Multiple sclerosis (MS) and ischemic stroke represent the most common pathophysiologies. While magnetic resonance imaging (MRI) allows for localizing lesions affecting the MLF, comprehensive comparative studies exploring potential different spatial characteristics of lesions affecting the MLF are missing until now. Methods We retrospectively investigated MRI examinations of 82 patients (40 patients with MS and 42 patients with ischemic stroke). For lesion localization, the brainstem was segmented into (1) ponto-medullary junction, (2) mid pons, (3) upper pons, and (4) mesencephalon. Results Corresponding lesions affecting the MLF were observed in 29/40 (72.5%) MS and 38/42 (90.5%) stroke patients. Compared to stroke patients, MS patients had significantly more lesions in multiple locations (P < .001). Stroke patients showed more lesions at the level of the mesencephalon (P < .001), while lesions at the level of the ponto-medullary junction, mid, and upper pons did not statistically differ between the groups. Conclusion Our results demonstrate that multiple lesions affecting the MLF make inflammatory-demyelination due to MS more likely, while lesion localization at the level of the mesencephalon favors ischemia.